Excessive usage of social media: a potential threat to mental health in Pakistan - Zafar, Habiba; Muhammad Bin Mobin (Journal of the Pakistan Medical Association, 2023)
Madam, Social media is an interactive technology that has been used for decades across the globe and Pakistan has millions of active users as well. Social media platforms have experienced rapid growth in Pakistan, with approximately 53 active million users in 2021, reflecting a 9.2% increase from the previous year [1]. While these platforms provide numerous benefits such as connectivity, information dissemination, and social support, they also pose risks to mental health and wellbeing. Studies have linked excessive social media use with increased levels of anxiety, depression and sleep disturbances [2]. The alarming increase in social media usage is a potential threat to the mental health and our population, particularly among young people. A study conducted on Pakistani university students revealed that excessive use of social media was significantly associated with increased stress, anxiety, and depression [3]. Furthermore, the prevalence of cyber bullying in Pakistan has now become a valid concern. One study estimating that most of Pakistani internet users, especially youth have experienced some form of cyberbullying [4]. Cyberbullying is a significant risk factor for mental health issues, including anxiety, depression, and suicidal ideation. Addiction to social media ultimately leads to exposure to a lot of harmful content; a study also showed that memes, cyber mobs and pranks are a common source of cyber-bullying causing more damage to the mental health of Pakistani students [5]. An extensive study also suggested the negative relationship between addiction of social media and mental health; users tend to have low self-esteem and confidence. Another disadvantage of excessive usage of social media is media violence; there is a lot of anger on media that can impact the mental health [6]. Given the potential impact of social media on mental health of Pakistani youth, the government should implement public awareness campaigns highlighting the potential risks of excessive social media usage and promoting healthy online behaviours. People who have already been diagnosed with any kind of mental illness due to excessive usage of social media should be properly treated and provided with therapies. More research on the impact of social media on mental health and well-being in Pakistan, this will help identify specific risk factors, protective factors and intervention strategies relevant to the Pakistani context.